2021
DOI: 10.3390/ijerph182111037
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Pedestrian Level of Service in the Context of Social Distancing: The Case of the City of Madrid

Abstract: During the COVID-19 pandemic, there has been a lot of discussion about keeping interpersonal distance to prevent the virus from spreading. To keep this interpersonal distance, authorities at different levels have taken measures to reduce people’s interactions, such as reducing capacities, curfews, pop-up cycle lanes, temporary pedestrianisation, and lockdowns. Many of these temporary measures have been perceived from a static view. Nevertheless, in a scenario of “new normality” or in the face of a possible new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…The delivered "shortest" (for moped) and "friendly" routes (for bikes and scooters) show that the journey planner works, although it is still in a beta version (under development). However, findings related to Madrid's dynamic show to be consistent with spatiotemporal travel patterns found in previous studies (Arias Romanillos, 2018Talavera-García & Pérez-Campaña, 2021).…”
Section: Resultssupporting
confidence: 91%
“…The delivered "shortest" (for moped) and "friendly" routes (for bikes and scooters) show that the journey planner works, although it is still in a beta version (under development). However, findings related to Madrid's dynamic show to be consistent with spatiotemporal travel patterns found in previous studies (Arias Romanillos, 2018Talavera-García & Pérez-Campaña, 2021).…”
Section: Resultssupporting
confidence: 91%
“…Uncovering spatio-temporal micromobility patterns using the Time Geography framework 579 can be observed, supporting what was also found by (Romanillos et al 2018;Talavera-García and Pérez-Campaña 2021). In the previous figure we also show the percentage of times that each location (hexagon) is a hot spot (with p-value 0,05) which enables us to quickly identify the most important areas of the city regarding micromobility departures (origin points).…”
Section: From a 2d Perspectivesupporting
confidence: 84%
“…Although PLOS models have been widely used in the literature, different studies have been conducted to improve the PLOS models based on different pedestrian needs. A Pandemic LOS has been developed using quantitative variables such as pedestrian space, walkway width, and speed to assess the PLOS during COVID-19 in the city of Madrid [17]. Nag et al (2020) [18] found that factors influencing pedestrian comfort can be categorised into three, including (1) flow characteristics of pedestrians and vehicular traffic, (2) physical elements of the built walking environment, and (3) users' perception of the walking environment.…”
Section: Literature Reviewmentioning
confidence: 99%